Nivel de riesgo cardiovascular según la escala de framingham en pacientes con diagnostico reciente de enfermedad renal crónica terminal en el Hospital Regional Docente de Trujillo, 2014 - Marquina Sánchez, Miguel Ángel (2016)
The worldwide prevalence of chronic kidney disease (CKD) is increasing, representing a burden on healthcare systems. Between 8 and 10% of the adult population suffers from kidney damage and every year millions die from complications associated with CKD, especially cardiovascular disease whose morbidity and mortality increases in direct proportion to the decline of renal function. To estimate that risk using classic factors according Framingham Score is the reason of this study. PROBLEM: What is the cardiovascular risk level in patients newly diagnosed with end-stage renal disease according to Framingham score? OBJETIVE: To determine the cardiovascular risk level in patients newly diagnosed with end-stage renal disease. MATERIAL AND MÉTHODS: Prospective descriptive study of patients newly diagnosed with ESRD treated at the HRDT during January-June 2014. Framingham Score was applied in selected patients reviewing in their medical history the criteria for that score. RESULTS: 43 patients were included by simple random sampling that meet the inclusion criteria. The average age was 54.8 years (SD ± 17.8) being more affected the women (53.5%). 48.8% of patients had an age ≥ 60 years. 14% had dyslipidemia by total cholesterol ≥ 200 mg/dL; and 72.1%, by HDL cholesterol ≤ 40 mg/dL. 86% had hypertension. 44.2% had type 2 diabetes mellitus and only 7% had a previous cardiovascular event. Finally, 51.2% had a high cardiovascular risk level, according to Framingham score. CONCLUSIONS: Most patients in the study has a high cardiovascular risk level according to the Framingham Score, mainly due to the coexistence of diabetes mellitus type 2 and/or previous cardiovascular event